INCREASED PRODUCTIVITY OF LIQUID SMOKE THROUGH FAST THAWING WITH REFRIGERATION SYSTEMS AT LOW AIR TEMPERATURE - Hidayati, Baiti; Sipahutar, Riman; Bizzy, Irwin; Faizal, Muhammad (Journal of Applied Engineering Science, 2021)
Liquid smoke increased in demand by the community because it is made from environmentally friendly waste can directly reduce the impact of environmental pollution. The smoke condensing process that is carried out conventionally using water can be continuously replaced using a refrigeration system, the smoke condensation process can be carried out using controlled low-temperature air, this can minimize machine space and energy. In this study, an analysis of variations in air temperature will be carried out to maximize the productivity of liquid smoke. The raw material for palm kernel shell is -4 + 5 mesh with cabin temperature variations of 15-10°C, 10-5°C, and 5-0°C and pyrolysis temperature of 300-400°C. Based on the research results obtained maximum results at a temperature of 5-0°C with 23.6% liquid smoke, 3.7% tar, 63.8% charcoal, and 8.9% gas. Based on the test results of chemical compounds, liquid smoke has an average phenol value of 56.59%. The lower the air temperature used to condense the smoke, the maximum liquid smoke will be and the less gas escapes to the air. It can directly reduce air pollution in the process of making liquid smoke.
Keywords: condensation, liquid smoke, low air temperature, palm shell, refrigeration